Selective cell recruitment and spatially controlled cell attachment on instructive chitosan surfaces functionalized with antibodies - Custódio, Catarina A. (2012)
Bioactive constructs to guide cellular mobilization and function have been proposed as an approach for a new generation of biomaterials in functional tissue engineering. Adult mesenchymal stem cells have been widely used as a source for cell based therapeutic strategies, namely tissue engineering. This is a heterogeneous cell population containing many subpopulations with distinct regenerative capacity. Thus, one of the issues for the effective clinical use of stem cells in tissue engineering is the isolation of a highly purified, expandable specific subpopulation of stem cells. Antibody functionalized biomaterials could be promising candidates to isolate and recruit specific cell types. Here we propose a new concept of instructive biomaterials that are able to recruit and purify specific cell types from a mixed cell population. This biomimetic concept uses a target-specific chitosan substrate to capture specific adipose derived stem cells. Specific antibodies were covalently immobilized onto chitosan membranes using bis[sulfosuccinimidyl] suberate (BS3). Quartz crystal microbalance (QCM) was used to monitor antibody immobilization/adsorption onto the chitosan films. Specific antibodies covalently immobilized kept their bioactivity and captured specific cell types from a mixed cell population. Microcontact printing allowed to covalently immobilize antibodies in patterns and simultaneously a spatial control in cell attachment